2021
DOI: 10.1590/1980-265x-tce-2020-0045
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Root Causes of Medication Errors and Falls in a Teaching Hospital: Cross-Sectional Study

Abstract: Objectives to characterize accidents/falls and medication errors in the care process in a teaching hospital and to determine their root causes and variable direct costs. Method cross-sectional study implemented in two stages: the first, was based on the analysis of secondary sources (notifications, medical records and cost reports) and the second, on the application of root-cause analysis for incidents with moderate/severe harm. The study was carried out in a teaching hospital in Paraná, which exclusively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
1
6
0
2
Order By: Relevance
“…Namely, for each additional type 2 error (scheduling error), hospitalization costs would increase by BRL 121.92, while for type 7 error (prescription error), hospitalization costs would increase by BRL 63.51. Other studies have confirmed this finding, verifying an increase in the average hospitalization cost associated with ME [ 15 , 35 , 37 ]. Interestingly, when analyzing these authors’ results, an increase in hospitalization costs correlated with the use of the ICU service and an average hospital stay longer than seven days, probably because these two factors lead to an increase in the use of technologies, more complex care, and increased hospital expenses.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Namely, for each additional type 2 error (scheduling error), hospitalization costs would increase by BRL 121.92, while for type 7 error (prescription error), hospitalization costs would increase by BRL 63.51. Other studies have confirmed this finding, verifying an increase in the average hospitalization cost associated with ME [ 15 , 35 , 37 ]. Interestingly, when analyzing these authors’ results, an increase in hospitalization costs correlated with the use of the ICU service and an average hospital stay longer than seven days, probably because these two factors lead to an increase in the use of technologies, more complex care, and increased hospital expenses.…”
Section: Discussionsupporting
confidence: 65%
“…Karthikeyan et al [ 33 ] reported prescription error frequencies ranging from 7.1 to 68.2%, as did Mekonnen et al’s [ 34 ] study, in which the average of prescription errors was 57.4% with a range between 22.8% and 77.8%. On the other hand, Pimentel et al [ 20 ] found a 29.7% incidence of scheduling errors and a 76.4% incidence of prescription errors in their study, whereas Paulino et al [ 35 ] reported a 27% incidence of dose omission errors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The results of the qualitative study phase further validated our quantitative findings. The literature confirms that there are organizational influences, created by management decisions, that have an impact on the safety of the entire care system and the provision of healthcare (Santiago and Turini, 2015;Paulino et al, 2021). In addition, the personal characteristics of healthcare professionals, patients and family members have been identified as factors in the variability of daily clinical practices (Salmond and Echevarria, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Falls cause injuries in almost half of the patients who are affected by this event, which may, in the most severe cases, lead to death (2). In addition, a fall can generate psychological impact by the fear of the patient falling again, which influences the risk of future falls (5), in addition to negatively interfering with the patient's functional capacity and mobility (6), which can increase the length of hospital stay and care costs, generating anxiety in the nursing team and producing repercussions on the institution's credibility, in addition to legal consequences (7,8).…”
Section: Introductionmentioning
confidence: 99%